Interactions between Type 1 Interferons and the Th17 Response in Tuberculosis: Lessons Learned from Autoimmune Diseases - Mourik, Bas C.; Lubberts, Erik; de Steenwinkel, Jurriaan E. M.; Ottenhoff, Tom H. M.; Leenen, Pieter J. M. (Frontiers in Immunology, 2017)
The classical paradigm of TB immunity, with a central protective role for Th1 responses and IFN-γ-stimulated cellular responses, has been challenged by unsatisfactory results of vaccine strategies aimed at enhancing Th1 immunity. Moreover, preclinical TB models have shown that increasing IFN-γ responses in the lungs is more damaging to the host than to the pathogen. Type 1 interferon signaling and altered Th17 responses have also been associated with active TB, but their functional roles in TB pathogenesis remain to be established. These two host responses have been studied in more detail in auto-immune diseases and show functional interactions that are of potential interest in TB immunity. In this review we first identify the roles type 1 interferons and Th17 immunity in TB, followed by an overview of interactions between these responses observed in systemic auto-immune diseases. We discuss (i) the effects of GM-CSF-secreting Th17.1 cells and type 1 interferons on CCR2+ monocytes; (ii) convergence of IL-17 and type 1 interferon signaling on stimulating B-cell activating factor (BAFF) production and the central role of neutrophils in this process; (iii) synergy between IL-17 and type 1 interferons in the generation and function of tertiary lymphoid structures and the associated follicular helper T-cell responses. Evaluation of these auto-immune-related pathways in TB pathogenesis provides a new perspective on recent developments in TB research.